THEORY OF SOCIAL ACTION IN THE MODERNIZATION PARADIGM EVOLUTION OF MODELS OF SOCIAL CHANGE IN THE MODERNIZATION PARADIGM - Vadim V. Arutyunyan (Вестник Северо-Кавказского федерального университета)
The article examines the impact of modernization on the changing patterns of human existence. The au- thor's attention is focused on the study of the causes and factors in both qualitative modernization of socio- historical transformation.